Student-Teacher Role Reversal at University Level-An Experience in Naval Engineering Education - Héctor Rubén Díaz Ojeda; Francisco Pérez-Arribas; Julio Pérez-Sánchez (MDPI AG, 2023)
The European Higher Education Area encourages a substantial change in the roles that students and teachers play at university. Student participation in the learning process should be primarily active, while teachers should adopt a guiding and mediating position. This paper describes a learning experience where an evolution of the roles of the trainers and learners is proposed. This methodology was implemented in the 2021/2022 and 2022/2023 university courses on the Bachelor in Naval Engineering. Students taking these courses are enrolled in the last year out of four of their Bachelor's and are given the task of changing their role from students to teachers by teaching a lesson. No previous knowledge about the lesson is required; therefore, this learning activity is a double challenge for the students, as they must, on the one hand, learn a new topic and, on the other hand, be able to explain the topic to their colleagues. Surveys related to the activity and the classmates' performance were carried out once the activity was completed. The results of the surveys show that students acquire technical knowledge more easily than traditional class and strengthen different skills, such as their self-esteem and communication ability. Additionally, the activity indicates the importance and necessity of boosting their autonomous work capacity, since they will be confronted with similar duties in their professional career. Finally, the proposed activity also reduces students' boredom in subjects that they are initially uninterested in.